(untitled) (Materiali di Estetica. Terza serie, 2019)
The essay identifies the notion of eclecticism as pivotal to Dorfles’ aesthetic research. A plurality of skills that has been traced since his formation and that generates the identikit of Dorfles as a restless explorer of contemporary languages: Dorfles as a critic, Dorfles as a scholar of aesthetics, Dorfles as a researcher of costume, industrial design, fashion, Dorfles as a painter and ceramist, Dorfles as a poet, Dorfles as an amateur musician, and even before all of that: Dorfles as a doctor and psychiatrist.